PENGARUH VIRAL MARKETING TOKOPEDIA MELALUI TIKTOK TERHADAP PERILAKU KONSUMEN GEN Z DI KOTA BATAM - Rys, Rismayana; Agustian Salim, Leon; Sefryanto, (PERFORMA, 2024)
This study aims to understand how TikTok's viral marketing strategy affects consumers' attitudes of Tokopedia. The purpose of this study is to clarify how the viral Tokopedia video on TikTok affects users' sense of information, entertainment, irritation, and credibility. This study uses a quantitative approach with a descriptive-causal goal. In this study, purposive sampling is combined with stratified dispropotional random sampling. The number of respondents in this survey is 391 individuals. To analyze this data, use SEM-AMOS 25.0 to perform descriptive and SEM analyses. The results show that informativeness, entertainment, and credibility fall into the good category, irritation falls into the slightly unfavorable category, and consumer behavior falls into the good category. The results of the SEM analysis indicate that Credibility, Entertainment, and Informativeness have positive and significant effects.